2017
DOI: 10.1097/moo.0000000000000329
|View full text |Cite
|
Sign up to set email alerts
|

What is the evidence for genetics in chronic rhinosinusitis?

Abstract: CRS is a multifactorial disease, with strong evidence of a genetic component in its pathophysiology for some cases. Currently, there are over 70 genes that have been genetically associated with CRS in the past 15 years. Future investigations into genetic causes and predispositions of CRS may allow for improved prognostication and development of disease-prevention strategies as well as novel therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 122 publications
1
8
0
Order By: Relevance
“…In particular, despite focusing on a specific subset of patients’ population (i.e., PCD cases), our data supported literature studies, thus confirming that AVI/AVI subjects are more susceptible to P. aeruginosa colonization as compared to the PAV/PAV ones [8, 13, 14]. In addition, recent studies highlighted that AVI haplotype is associated with gram-negative bacterial infections in patients suffering from CRS, a common disease characterized by chronic inflammation of nasal mucosa and paranasal sinuses [14, 23]. Moreover, TAS2R38 genotype was reported as an independent risk factor for CRS patients failing medical therapy and requiring surgical intervention [12].…”
Section: Discussionsupporting
confidence: 86%
“…In particular, despite focusing on a specific subset of patients’ population (i.e., PCD cases), our data supported literature studies, thus confirming that AVI/AVI subjects are more susceptible to P. aeruginosa colonization as compared to the PAV/PAV ones [8, 13, 14]. In addition, recent studies highlighted that AVI haplotype is associated with gram-negative bacterial infections in patients suffering from CRS, a common disease characterized by chronic inflammation of nasal mucosa and paranasal sinuses [14, 23]. Moreover, TAS2R38 genotype was reported as an independent risk factor for CRS patients failing medical therapy and requiring surgical intervention [12].…”
Section: Discussionsupporting
confidence: 86%
“…There is mounting evidence to suggest that CRS may have a genetic basis. 60,61 The largest number of genetic loci associated with CRS are genes related to inflammation. 62 A review of the genetics of CRS by Hsu et al 62 illustrates that many independent studies have found CRS to be associated with polymorphisms in the major histocompatibility complex genes necessary for antigen-specific adaptive immune responses, genes involved in innate immunity, and other genes related to specific inflammatory pathways or mediators (eg, cytokines).…”
Section: Genetic Risk For Crsmentioning
confidence: 99%
“…There is a strong association of a homozygous mutation of the chloride transport gene (CFTR) with childhood-onset CRS (Kim and Ober, 2019). Heterozygous CFTR mutations are also associated with CRS signals, albeit less than in clinical CF, with disease usually presenting in adulthood (Hsu et al, 2013;Yoo and Suh, 2017). The impaired mucociliary flow seen with CFTR mutations is presumed to intensify microbial exposure, also affecting disease course (Wang et al, 2000).…”
Section: Epithelial Functions In Bronchiectasis Primary Ciliary Dyskmentioning
confidence: 99%